Efektifitas Ombudsman dalam Pengawasan Kepolisian Pada Penanganan Maladministrasi (Studi Kasus Muhammad Lestaluhu) - Razka Aditya Ahmad; Anggreini Gema Dzikrillah; Kezia Resiocta Sehati (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Ombudsman is an institution tasked with monitoring the administration of public services provided by state and government authorities, including those held by public companies or local businesses. The Ombudsman's success target is to improve services and increase public satisfaction with public services. Control by the ombudsman over the provision of public services is a type of external oversight that is repressive in nature. This is because the bodies outside government agencies that are further examined carry out ombudsman supervision. The Ombudsman carries out supervision based on public reports regarding bad behavior or maladministration of public officials, then the Ombudsman monitors or enforces laws and regulations against irregularities committed by the administration of public services.